A MODEL FOR TSUNAMI GENERATION BY BOTTOM MOVEMENTS INCORPORATING WATER COMPRESSIBILITY - Nosov M.A. (My University, 1999)
A comparative study of wave excitation by bottom movements in a compressible and an incompressible perfect fluid was carried out using a linear potential theory. An analysis of the resulting exact analytical solutions showed significant differences between the compressible and incompressible fluid behaviors under the conditions inherent in real tsunami sources.